PENGARUH LKPD BERBASIS DISCOVERY LEARNING TERHADAP PEMAHAMAN KONSEP MATA PELAJARAN IPAS PADA PESERTA DIDIK KELAS V SEKOLAH DASAR - Nur Safitri, Nadia; Izzatika, Amrina; Wahyudi, Apri; Khairani, Fadhilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low conceptual understanding of fifth grade students in the Science and Social Studies (IPAS) subject was one of the problems identified at SD Negeri 1 Nunggalrejo. This study aimed to determine the effect of Discovery Learning based student worksheets (LKPD) on students' conceptual understanding. This research employed a quasi experimental method using a nonequivalent control group design. The population consisted of 40 fifth grade students of SD Negeri 1 Nunggalrejo, all of whom were selected as the research sample through a saturated sampling technique. Data were collected through conceptual understanding tests and observation sheets. Data analysis was conducted using simple linear regression analysis. The results showed that the use of Discovery Learning based LKPD had a significant effect on students' conceptual understanding in the IPAS subject for fifth-grade students at SD Negeri 1 Nunggalrejo in the 2025/2026 academic year. The results showed a higher improvement in conceptual understanding in the experimental class than in the control class, with an average N-Gain score of 0.46 in the experimental class and 0.36 in the control class. The results of the simple linear regression test indicated that the calculated F value (31.393) was greater than the F-table value (4.41), with a significance value of < 0.001. Therefore, H₀ was rejected and Hₐ was accepted. Therefore, Discovery Learning based LKPD can be used as an effective learning alternative to improve students conceptual understanding in IPAS learning.